Gall-Bladder Agenesis and Associated Anomalies. Issue 4 (1995) - Yiangou, Constantinos; Shorey, Brian; Spigelman, Allan D.
Abstract : Congenital absence of the gall-bladder is a rare condition. It is sometimes associated with other congenital defects. We report here two cases of gall-bladder agenesis discovered at laparoscopy. Both had a history of skeletal and cardiovascular anomalies. The investigation of patients with absent gall-bladder can be very difficult. Ultrasound scanning is usually inconclusive and further noninvasive tests should be performed to establish the diagnosis and prevent an unnecessary operation. The presence of other congenital defects should alert the clinician to the possibility of gall-bladder agenesis.